2015
DOI: 10.1007/s13197-015-1727-1
|View full text |Cite
|
Sign up to set email alerts
|

Plantain peel - a potential source of antioxidant dietary fibre for developing functional cookies

Abstract: Plantain cultivar Nendran is popular as a staple food in many parts of India and deep fried chips made from raw matured Nendran are one of the popular snack items in India. This study aims to utilize peel from Nendran variety- the main byproduct of banana chips industry- to develop high fibre cookies with enhanced bioactive content. Proximate analysis indicated that peels are rich in total dietary fibre (64.33 g/100 g), vitamins (Folic acid- 33.12 mg/100 g) and minerals (Potassium- 35.61 mg/100 g). Nendran Pee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 27 publications
6
51
0
3
Order By: Relevance
“…Corresponding to the TPC results, EtOAcE was also identified as containing the highest amount of TFC, this being 86.91 QE mg g −1 DW, which is significantly different ( P < 0.05) from the other three extracts, which were ranked as PEE (37.58 QE mg g −1 DW), EE (26.55 QE mg g −1 DW), and WE (3.62 QE mg g −1 DW) in descending order. This result indicates that ethyl acetate is a good solvent for flavonoid extraction, which was consistent with a previous finding showing that the TFC of Plantain peel extracts varied depending on the extracting solvents used, the order being ethyl acetate (9.39 QE mg g −1 DW) > methanol (1.71 QE mg g −1 DW) > hexane (0.91 QE mg g −1 DW) . As in our present report of TFC in EE (26.55 QE mg g −1 DW), the TFC of the methanolic extract of Citrus aurantifolia peel collected from various locations in Italy ranged between 23.5 and 52.1 QE mg g −1 DW, while the TFC of 80% methanol extract of the peels of 14 wild mandarin genotypes native to China varied from 7.95 to 20.66 QE mg g −1 DW, all of these quantities being less than those of EtOAcE (86.91 QE mg g −1 DW).…”
Section: Resultssupporting
confidence: 93%
“…Corresponding to the TPC results, EtOAcE was also identified as containing the highest amount of TFC, this being 86.91 QE mg g −1 DW, which is significantly different ( P < 0.05) from the other three extracts, which were ranked as PEE (37.58 QE mg g −1 DW), EE (26.55 QE mg g −1 DW), and WE (3.62 QE mg g −1 DW) in descending order. This result indicates that ethyl acetate is a good solvent for flavonoid extraction, which was consistent with a previous finding showing that the TFC of Plantain peel extracts varied depending on the extracting solvents used, the order being ethyl acetate (9.39 QE mg g −1 DW) > methanol (1.71 QE mg g −1 DW) > hexane (0.91 QE mg g −1 DW) . As in our present report of TFC in EE (26.55 QE mg g −1 DW), the TFC of the methanolic extract of Citrus aurantifolia peel collected from various locations in Italy ranged between 23.5 and 52.1 QE mg g −1 DW, while the TFC of 80% methanol extract of the peels of 14 wild mandarin genotypes native to China varied from 7.95 to 20.66 QE mg g −1 DW, all of these quantities being less than those of EtOAcE (86.91 QE mg g −1 DW).…”
Section: Resultssupporting
confidence: 93%
“…The replacement of wheat flour by GP promoted a dose-dependent increase in phenolics contents guava breads (Table 1). Similar, increase in phenolic compounds in baking products incorporated with fruits powders was reported (Arun et al 2015;Bhol et al 2016;Platat et al 2015;Rupasinghe et al 2008).…”
Section: Soluble and Insoluble Phenolic Compoundssupporting
confidence: 79%
“…Unripe banana and plantain peel presented an increase in the TDF in banana peel during fruit ripening and in some cases there was a decrease in the TDF (Happi-Emaga et al, 2007). Flour prepared with matured plantain cultivar peels showed the highest TDF content (643 g/kg) reported to date (Arun et al, 2015). It was concluded that the TDF in the peel depends on various factors such as cultivar and ripening stage apparently due to the higher TDF content in the banana group with respect to the plantain group (Happi-Emaga et al, 2007).…”
Section: Resultsmentioning
confidence: 91%
“…These antioxidant environments produced by microbiota have been reported to prevent against oxidative process, preserve tissues, and reduce the development of colon cancer. Recently, extracts of matured plantain flour peels using methanol showed higher cupric ion reduction (2.36 μM TR/g dry weight), followed by ethyl acetate extract (1.41 μM TR/g dry weight); however, when extracting with hexane, no antioxidant activity was observed (Arun et al, 2015).…”
Section: Polyphenols Content and Antioxidant Capacitymentioning
confidence: 99%
See 1 more Smart Citation